GAYA KEPEMIMPINAN DAN MOTIVASI PENGARUHNYA TERHADAP KINERJA KARYAWAN BAGIAN WAREHOUSE PADA PT.SHIN HWA BIZ SERANG BANTEN - Muhammad Saleh; Abdul Bahits; Fatari Fatari (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine how much influence leadership style and motivation have on the performance of warehouse employees at PT. Shin Hwa Bus Serang-Banten. This study uses a quantitative approach using survey methods with a saturated sample where the population is used as a sample, namely 45 respondents. Data collection techniques are primary data. The analysis technique used is multiple linear regression analysis, correlation coefficient, t test, f test and coefficient of determination. previously carried out classical assumption tests consisting of normality tests, multicollinearity tests, and heteroscedasticity tests. The results of the research on leadership style and motivation variables have a partially significant effect on employee performance. Evidenced by the magnitude of the T-count test of leadership style of 5.764 and work motivation of 2.621 which is greater than the Ttable of 2.016. Simultaneously a significant influence on employee performance, as evidenced by Fcount>Ftable or 24.425>3.219. Partially the comparison of tcount and ttable shows that the leadership style variable is tcount>ttable or 5.764>2.016 and the motivational variable is tcount>ttable or 2.621>2.016